The emotional dance with depression: A longitudinal investigation of OULA® for depression in women. Issue 4 (October 2020) - Hellem, Tracy; Sung, Young-Hoon; Ferguson, Hayden; Hildreth, Laura
Abstract: The primary purpose of this pilot study was to evaluate OULA®, a dance fitness program with a strong emphasis on processing emotions through dance, as an intervention for depression in women diagnosed with major or persistent depressive disorders. 53 women were eligible for participation. Women attended OULA® for 12 weeks and then abstained from OULA® during week 13. For the primary outcome, depression severity was measured using the Hamilton Depression Rating Scale (HAM-D), and secondary outcomes were measured using the Beck Anxiety Index (BAI) and the Subjective Happiness Scale (SHS). After the abstinence week, women were offered 3-months of optional additional OULA®. HAM-D, BAI and SHS scores were collected at weeks 2, 4, 5–14 and at the end of the 3-month optional OULA® phase. Results from linear mixed effects repeated models show that during the 12-week intervention period and at week 26, HAM-D scores significantly decrease each week compared to baseline. Further, BAI scores significantly decrease starting at week 5 and through the end of the intervention period and at week 26. Moreover, SHS scores increased significantly for four of the weeks during the intervention period and at week 26. The results from this study suggest that OULA® may be a useful intervention for decreasing depression and anxiety severity in women with depression but may not be helpful for improving subjective happiness.